RADIOGRAPHIC EVALUATION OF BONE FILLING IN INTRABONY PERIODONTAL DEFECTS WITH CERABONE® AS BONE REPLACEMENT GRAFT: CASE SERIES - Hristina Maynalovska; Christina Popova; Antoaneta Mlachkova (Peytchinski Publishing, 2022)
The regeneration of lost periodontal tissues due to periodontal disease remains a difficult clinical challenge. As clinicians, we look for procedures with improved predictability, beneficial impact on the treatment of periodontal disease, and in the long term - improvement of prognosis of the involved teeth. Various types of grafting materials with substantial research evidence reporting on their efficacy have been introduced in regenerative periodontal therapy based on their ability to facilitate the reconstruction of the lost supporting apparatus. Consequently, the periodontal regeneration of intrabony defects involves not only the experience and skills of the clinicians but also the selection of suitable regenerative material. The type of tissue filling in a periodontal defect after surgical treatment can only be precisely evaluated by histological means, and it is restricted to a few cases due to ethical reasons. Histologic studies have demonstrated regeneration potential for GTR, allografts, xenografts and growth factors. And since the periodontal regeneration includes the regrowth of alveolar bone, by using radiographs, changes of the alveolar crest may be used to monitor periodontal healing. Our case series present the radiographic evaluation of the bone fill of 6 vertical bone defects treated with Cerabone®. The xenograft Cerabone® is a 100% pure bone mineral of bovine origin that has been successfully applied in regenerative dentistry and has been in use for more than 15 years in various medical applications (e.g. craniofacial surgery, oncology and hand and spine surgery).